PERSEPSI PENGUNJUNG TERHADAP PENGELOLAAN OBJEK WISATA GUNUNG MAHAWU DI KOTA TOMOHON - Jemmy Rudolf Pangemanan; Alma Karangan Pongtuluran; Margresya Diana Rompas; Kevin Keril Pangemanan; Silvana Audry Rima Wewengkang; Towoliu, Benny Irwan (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
Tomohon is a city located in North Sulawesi Province, which is unique in that it has no ocean but is flanked by two volcanic mountains, Mount Lokon and Mount Mahawu. Both mountains are still active, but are considered to provide fertility for agriculture and plantations for local residents. Mahawu Mount has been designated as a special interest tourist attraction, where the local government has arranged infrastructure and facilities. However, the availability of existing facilities does not guarantee good management of the area, there are still many things that need attention. The purpose of this study was to examine visitor perceptions of the management of the Mahawu Mount tourist attraction facilities in Tomohon City. This research method uses a survey method conducted on 100 respondents who visit tourist sites.  The research instruments used were questionnaires and observations.  The  Likert scale is used to categorize each question, as well as the use of score interpretation to facilitate answers to respondents' assessments. The analysis used is descriptive, using tables and percentages.